The aesthetic of nomadism and the logic of perception in creative action (Recurrences in the geographies of the sensed) - Chaima Mohammed Al-Taher Zaafouri (Basrah Arts Journal, 2023)
The artwork was born from the womb of flat surfaces that have neither specific direction nor destination. It emanates from infinite chaotic surfaces, overlapping and contradicting, intertwining and entwining vertically and horizontally in ways that are not subject to logical geometrical norms. Despite all the chaos and emptiness, existence remains steadfast in its elements and its primitive colors because of its interchangeable event. Art does not differ from nature. Perception brings them together in a mixture of colors on the surface of the painting. The artist transfers his infinite perceptions to an expression of what draws man to the world to endless ideas and sensations expressing the instinctive inattentiveness of existence. As it is an artistic event multiplying the desire to seek victory in the world and belief in life in its diversity, dissonance, and multiplicity. It validates life against death, consolidates fun, and exalts joy and forces of nature against transcendence and divine ethics.